48.5k views
3 votes
Can I get some help on how to solve this?

Can I get some help on how to solve this?-example-1

1 Answer

2 votes

Answer:

see explanation

Explanation:

Factorise both denominators

x² + 2x = x(x + 2) ← common factor of x

x² - 4 = (x - 2)(x + 2) ← difference of squares

Before subtracting we require common denominators

Multiply the numerator/denominator of the first fraction by (x - 2)

Multiply the numerator of the second fraction by x

=
(5)/(x(x-2)(x+2)) -
(2x)/(x(x-2)(x+2))

Distribute and simplify the numerator leaving the denominator

=
(5x-10-2x)/(x(x-2)(x+2))

=
(3x-10)/(x(x-2)(x+2))

User Amolbk
by
5.8k points